Under surveillance: Does Global Positioning System monitoring of offenders reduce recidivism? - Hawkes, Anna L; Sellbom, Martin; Gilmour, Fairleigh E (Criminology & criminal justice, 2024)
Appropriate supervision is critical in offender management, but requires effective tools to guide decisions and interventions. This research project investigated the effectiveness of Global Positioning System monitoring in reducing re-offending, while considering the impact of Global Positioning System monitoring on the offender’s well-being. The method consisted of evaluating a matched sample of Global Positioning System monitored offenders (n = 220) versus non-Global Positioning System1 monitored (n = 219) subject to extended supervision and parole orders over a 24-month follow-up period. All participants were male offenders released from prison within New Zealand. The results showed statistically significant differences for ‘non-violent’ and ‘violent’ re-offending rates, with Global Positioning System monitoring being associated with lower rates of recidivism. There was no evidence of increased distress in those men subject to Global Positioning System monitoring. This study provides novel information about Global Positioning System monitoring and contributes to our understanding of how this tool can reduce recidivism.